2003
DOI: 10.1074/jbc.c300148200
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Type 1 Inositol 1,4,5-Trisphosphate Receptor Revealed by Electron Cryomicroscopy

Abstract: The three-dimensional structure of the type 1 inositol 1,4,5-trisphosphate receptor (InsP 3 R1) has been determined by electron cryomicroscopy and single-particle reconstruction. The receptor was immunoaffinity-purified and formed functional InsP 3 -and heparin-sensitive channels with a unitary conductance similar to native InsP 3 Rs. The channel structure exhibits the expected 4-fold symmetry and comprises two morphologically distinct regions: a large pinwheel and a smaller square. The pinwheel region has fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(83 citation statements)
references
References 28 publications
5
77
1
Order By: Relevance
“…Recent studies have also demonstrated the square-like (29) and the windmill-like three-dimensional maps (28,30). These two structures strongly support our hypothesis of global conformational changes within IP 3 R. The comparison between the S-state and W-state suggests that the structural transition from square to windmill is caused by the relocation of functional domains.…”
Section: Fig 1 Effects Of Casupporting
confidence: 66%
See 2 more Smart Citations
“…Recent studies have also demonstrated the square-like (29) and the windmill-like three-dimensional maps (28,30). These two structures strongly support our hypothesis of global conformational changes within IP 3 R. The comparison between the S-state and W-state suggests that the structural transition from square to windmill is caused by the relocation of functional domains.…”
Section: Fig 1 Effects Of Casupporting
confidence: 66%
“…Accumulating reports have explicitly demonstrated two distinct structures of IP 3 R. One is square-shaped (26,27,29), and the other is windmill-shaped (24,27,30). We have postulated that these dual structures are attributable to global conformational changes between the square state (S-state) and windmill state (W-state) within tetrameric IP 3 R particles as described previously (27).…”
Section: ؉mentioning
confidence: 99%
See 1 more Smart Citation
“…Functional IP 3 Rs are tetrameric, assembled either from identical subunits or from mixtures of the three subtypes and their many splice variants Foskett et al 2007). Several structures of the entire IP 3 R1 have been published, each derived from single particle analysis of images from electron microscopy (Hamada and Mikoshiba 2002;Jiang et al 2002a;da Fonseca et al 2003;Hamada et al 2003;Serysheva et al 2003;Sato et al 2004). These studies confirm the tetrameric state of IP 3 R, but variability between the structures and their relatively low resolution ( 30 Å ) have, so far, limited any realistic interpretation of the structural basis of IP 3 R activation (Fig.…”
Section: Structural Determinants Of Ip 3 R Activationmentioning
confidence: 99%
“…Other eukaryotic homotetrameric ion channels have a twolayer architecture with distinct cytoplasmic and membraneembedded domains, including potassium channels, the InsP 3 receptor, and the ryanodine receptor (28)(29)(30)(31)(32)(33).…”
Section: Overexpression and Purification Of Tetrameric Trpv1mentioning
confidence: 99%